Social Policy in Settled and Transitional Countries: A Comparison of Institutions and their Consequences - Olli Kangas (Luxembourg Income Study (LIS), 1999)
In all societies people seek shelter against such risk where their livelihood is for some reason endangered. Childhood, sickness, accidents, and old age are classical examples of social risks that a society somehow must encounter. A society that does not take care of its vulnerable members is not a sustainable one. Therefore, some kind of collective risk pooling and collective safety nets are necessary for a society to sustain itself. The structure of our study is as follows: Firstly, we describe the data used in this study. Secondly, in order to set the study of social policy in a wider frame of references it is fruitful to inspect economic development in post- socialist countries and in western nations. Thereafter follows a section on institutional arrangements guaranteeing social protection in case of old-age, sickness, childbirth, and unemployment. Fourthly, in addition to institutional set ups we are interested in analyzing the effectivity of those institutions. Effectivity will be measured by using some standard methods in this field of study: income distribution and poverty. Moreover, we will study the effectivity of social transfer systems to alleviate poverty in various countries. Fourthly, and lastly, we are interested in the costs of social security. What are the total costs and how is the burden divided between different sources of financing? What is the proportion of the insured, employers, and the public sector in the financing of social security in different countries?
Keywords: 330; Sozialpolitik; Institutionelle Infrastruktur; Einkommensverteilung; Wirkungsanalyse; Vergleich; Industrieländer; Transformationsstaaten